Comprehensive comparative analysis of histopathology and gene expression in subchondral bone between kashin-beck disease and primary osteoarthritis - Yang, Lei; Sun, Jingwen; Zhang, Ying; Guo, Xiong; Zhao, Guanghui (Frontiers in Genetics, 2022)
Kashin-Beck disease (KBD) is an endemic, degenerative osteoarthropathy that exhibits some similar characteristics to osteoarthritis (OA) but with different etiologies and pathogeneses. In addition to cartilage damage, microstructural changes of bone were observed in KBD. This study aimed to comparatively demonstrate the general histopathological changes, transcriptomics, and differentially expressed miRNAs of subchondral bone between KBD and OA. Tibial plateau subchondral bone samples were collected from eighteen patients with KBD and eighteen patients with OA. Histopathological changes were examined by hematoxylin-eosin (HE) staining, safranin O-fast green staining, and picrosirius red staining. RNA sequencing and miRNA array analysis were performed to screen the differentially expressed genes (DEGs) and differentially expressed miRNAs (DEMs), respectively. The subchondral bone samples of the tibial plateau of KBD and OA both showed increased thickness and sclerosis. A total of 179 DEGs and 124 DEMs were identified in subchondral bone between KBD and OA, which were involved in several vital GO terms and KEGG signaling pathways. Our results suggest that the pathological mechanisms of subchondral bone are different between KBD and OA, although they exhibit similar histopathological features. Integrated analysis revealed several genes such as ADAMTS14, SLC13A5, and CEACAM1, that may be crucial DEGs in subchondral bone between KBD and OA, suggesting that these genes could serve as potential differential diagnostic biomarkers for subchondral bone lesions in KBD and OA. These findings provide valuable information for further clarifying pathological changes in subchondral bone in KBD and OA.